Pemanfaatan Sampah Rumah Tangga Melalui Praktik Eco-Enzym Di Karang Jalak Mekar Kelurahan Sunyaragi Kota Cirebon - Munawaroh; Fadilah, Lulu; Purnama Fuad, Muhammad Darlis; Pidianti, Depi; Suryadi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Domestic waste or household waste is waste left over from human activities. Household waste can be solid or liquid. Currently, the problem in the city of Cirebon is waste where in 2023 the percentage is still the same, reaching more than 200 tons per day. Therefore, the purpose of this Eco-Enzym Socialization and Practice activity is none other than to raise awareness that household waste will be very useful if managed properly. In addition to raising awareness, this activity also aims to provide education about eco-enzymes that are beneficial to life. The method used in implementing the program is the PAR (Participatory Action Reseacrh) method. PAR can also be called research by the community, with the community and for the community, not empowerment of the community. The targets in this activity are PKK and Posyandu cadres in Rw 07 Karang Jalak Mekar, Sunyaragi Village, Cirebon City. The implementation of this activity was quite optimal in Rw 07 because in the initial condition they did not understand the utilization of waste into fermented eco enzyme. After this activity, Rw 07 cadres understand what is called eco enzyme and its benefits so that they can immediately practice the eco enzyme.